Модель выбора набора ИТ-сервисов для конечных пользователей - Левыкин, В. М.; Юрьев, И. А. (My University, 2016)
У статті розглядаються питання вибору набору ІТ-сервісів для кінцевих користувачів інформаційної системи. Розроблено модель вибору набору ІТ-сервісів для кінцевих користувачів. Описано всі елементи розробленої моделі та їх взаємодія в процесі вибору набору ІТ-сервісів. Представлена ієрархічна структура критеріїв оцінки ІТ-сервісу. Представлена реалізація розробленої моделі з застосуванням методу парних порівнянь. The article deals with the selection of a set of IT services for end-users of information systems. The model of selecting a set of IT services to end users was developed. All the elements of the developed model was describe, and their interaction in the process of selecting a set of IT services. A set of high-quality IT services means their best set of features and characteristics that meet the stated needs of the enterprise. Enterprise requirements are determined by its business strategy. IT services is a set of software, which has the same functionality corresponds to a plurality of end user requirements. This set is determined by the requirements of end-users to support business processes, which are performed as part of their job descriptions. A paper presents a hierarchical structure of criteria for evaluating IT service. Presents the implementation of the developed model using the method of paired comparisons.
Keywords: ІТ-сервіс; інформаційна система; кінцеві користувачі